PENERAPAN COLLABORATIVE STRATEGIC READING (CSR) BERBANTUAN PLATFORM BOOK CREATOR UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V UPT SPF SD INPRES PARANG KOTA MAKASSAR - Nurul Amalia; Widya Karmila Sari Achmad; Rosdiah Salam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low reading comprehension skills of fifth-grade students at UPT SPF SD Inpres Parang, Makassar. The purpose of this study was to improve students’ reading comprehension skills through the implementation of Collaborative Strategic Reading (CSR) assisted by the Book Creator platform. This study employed a qualitative approach with the type of classroom action research (CAR) conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The subjects of this study were one classroom teacher and 15 fifth-grade students. The data were collected through observation, tests, and documentation, using observation sheets and reading comprehension tests as instruments. The data were analyzed through three stages: data reduction, data display, and conclusion drawing. The results of the study showed an improvement in both teacher and student activities in implementing CSR assisted by the Book Creator platform, increasing from the fair (C) category to the good (B) category according to the implementation target. In addition, students’ reading comprehension test results improved from cycle I to cycle II, achieving a mastery level of 80%, which exceeded the minimum target of ≥70%. Thus, it can be concluded that the implementation of Collaborative Strategic Reading (CSR) assisted by the Book Creator platform can improve the reading comprehension skills of fifth-grade students at UPT SPF SD Inpres Parang, Makassar.